STUDI KASUS : PROGRAM FISIOTERAPI PADA PNEUMOTHORAKS DENGAN INTERVENSI DIAPHRAGMA BREATHING EXERCISE DAN MOBILISASI SANGKAR THORAKS - Dwi Panulat, Pandu; Mulya Fatah, Faisal (Jurnal Kesehatan An-Nuur, 2026)
Pneumothorax is a medical condition characterized by the presence of air in the pleural cavity, causing lung collapse and respiratory distress. This case is often associated with pulmonary tuberculosis as a secondary cause. This study aims to evaluate the effectiveness of physiotherapy interventions in the form of Diaphragma Breathing Exercise and thoracic cage mobilization in reducing shortness of breath, increasing thoracic expansion, and increasing functional activity in pneumothoracic patients with a history of tuberculosis. This case study was conducted on a 54-year- old female patient with a diagnosis of dextra pneumothorax at Fatmawati Hospital. The intervention was given at 4 meetings, with outcome measurement using the Borg Scale for shortness of breath, anthropometry for thoracic expansion, and Barthel Index for functional activity. The results showed a decrease in the degree of shortness of breath from a value of 5 (weight) to 3 (moderate), an increase in thoracic expansion in the measurement of axilli (1.2 cm to 1.6 cm), papilla (1.2 cm to 1.5 cm), and proceso xypoideus (2 cm to 2.2 cm), as well as stabilization of functional activity with a Barthel Index score of 11 (moderate dependence).